N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung